2013
DOI: 10.1021/ol400576e
|View full text |Cite
|
Sign up to set email alerts
|

Reductive Homocondensation of Benzylidene- and Alkylidenepyruvate Esters by a P(NMe2)3-Mediated Tandem Reaction

Abstract: A reductive homocondensation of E-benzylidenepyruvate esters mediated by P(NMe2)3 is described. The transformation, initiated by the Kukhtin-Ramirez addition of the phosphorus reagent to the vinyl-substituted α-dicarbonyl substrate, proceeds via a resonance delocalized oxyphosphonium dienolate intermediate to provide access to diverse oxygenated heterocycles as a function of the substituent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(19 citation statements)
references
References 39 publications
(21 reference statements)
0
19
0
Order By: Relevance
“…Based on our current and previous findings, as well as those reported by Ramirez , Scheidt , Radosevich , and Xiao , our working mechanistic hypothesis addresses two possible competing pathways en route to dihydroindole formation ( Scheme ). Addition of P(NMe 2 ) 3 to formate 1a leads to an equilibrium between dioxaphospholene 11a and oxyphosphonium enolate 11b , of which the enolate is the presumptive reactive constitutional isomer.…”
Section: Resultsmentioning
confidence: 62%
See 2 more Smart Citations
“…Based on our current and previous findings, as well as those reported by Ramirez , Scheidt , Radosevich , and Xiao , our working mechanistic hypothesis addresses two possible competing pathways en route to dihydroindole formation ( Scheme ). Addition of P(NMe 2 ) 3 to formate 1a leads to an equilibrium between dioxaphospholene 11a and oxyphosphonium enolate 11b , of which the enolate is the presumptive reactive constitutional isomer.…”
Section: Resultsmentioning
confidence: 62%
“…[25 -29] Inspired by Scheidt and coworkers elegant enantioselective assembly of benzopiperidinones employing Supporting information for this article is available on the WWW under https://doi.org/10.1002/hlca.201900192 an NHC-catalyzed [4 + 2]-cycloaddition of in situ generated aza-o-quinone methides (aza-o-QM) and aliphatic carboxylic acids (Scheme 2,a), and building on our previous work toward dihydrobenzofurans (Scheme 2,b), we speculated that aza-o-QMs could serve as 1,3-heterodienes in the construction of 2,3-dihydroindoles employing readily accessible oxyphosphonium enolates as C 1 synthons. [25,27,[30][31][32][33][34][35][36][37][38] Herein, we report the successful development of a phosphorus(III)-mediated redox construction of 2,3-dihydroindoles resulting from the addition of 2-amino benzyl halides to 1,2dicarbonyls (Scheme 2,c). The resulting (4 + 1)-cycloaddition represents a complementary method for heterocycle assembly and adds to the growing ensemble of synthetic methods based on Kukhtin -Ramirez-like reactivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…359 Photoreaction of cyclopropylmethyl 2-oxo-2-phenylacetate was investigated in the presence of O 2 in benzene, in which a mixture of products was obtained along with 4,5-dihydrooxepin-2(3H)-one 905 in low yield. The reaction proceeded by γ-H abstraction (903), followed by ring opening of cyclopropylmethyl moiety to form intermediate 904, which underwent cyclization to afford 4,5-dihydrooxepin-2(3H)-one 905 (Scheme 291).…”
Section: Oxepinsmentioning
confidence: 99%
“…This reaction is known as Kukhtin-Ramirez addition which have been the issues of numerous investigations. 16 The reaction of B with electrophilic reagents yields alkoxyphosphonium species C which acts as an electrophile for nucleophilic displacement. 17 Based on the importance of the PRs in new organic synthesis, and because of their vital effect as efficient catalysts in Kukhtin-Ramirez addition, a comprehensive kinetic and thermodynamic study has been carried out on the effects of PRs in the reaction which reported by Zhang and coworkers.…”
Section: Introductionmentioning
confidence: 99%